2016
DOI: 10.1093/bjsw/bcw083
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Communication between Social Workers, Children and Young People

Abstract: A key issue for the social work profession concerns the nature, quality and content of communicative encounters with children and families. This article introduces some findings from a project funded by the Economic and Social Research Council (ESRC) that took place across the United Kingdom between 2013 and 2015, which explored how social workers communicate with children in their everyday practice.The Talking and Listening to Children (TLC) project had three phases: the first was ethnographic, involving obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 15 publications
0
56
1
1
Order By: Relevance
“…She was aware of Kohli's (2007) discussion of the "thin" stories asylum seekers tell to the authorities, stories from which much of the detail, complexity, and contradiction have been removed to make them easier to "sell." Winter et al (2017) found that some children refused to speak to the social worker because they were seen as a hostile intruder. This, in turn, is drawn from Geertz's (1973) work on the importance of richly detailed and contextualized "thick" descriptions of other cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…She was aware of Kohli's (2007) discussion of the "thin" stories asylum seekers tell to the authorities, stories from which much of the detail, complexity, and contradiction have been removed to make them easier to "sell." Winter et al (2017) found that some children refused to speak to the social worker because they were seen as a hostile intruder. This, in turn, is drawn from Geertz's (1973) work on the importance of richly detailed and contextualized "thick" descriptions of other cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ethnographies of home visits have highlighted this as a particularly problematic area for social workers who may lack the skills and confidence (Ferguson, 2016) and may be faced with children who refuse to communicate out of hostility (Winter et al, 2017) or, as the case study here illustrates, the nearby presence of a parent. Recent ethnographies of home visits have highlighted this as a particularly problematic area for social workers who may lack the skills and confidence (Ferguson, 2016) and may be faced with children who refuse to communicate out of hostility (Winter et al, 2017) or, as the case study here illustrates, the nearby presence of a parent.…”
Section: Home Visiting In Social Workmentioning
confidence: 98%
See 1 more Smart Citation
“…The talking and listening to children project practice in this context (Ruch et al, 2017;Winter et al, 2016). The talking and listening to children project practice in this context (Ruch et al, 2017;Winter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the (often unintended) consequences of these developments and their impacts on day-to-day practice with children and families have been highlighted, with findings from a range of studies pointing to the fragmentation and sanitisation of practice (Broadhurst, Hall, Wastell, White, & Pithouse, 2010;Cooper & Lees, 2015;Hall, Parton, & White, 2010;Peckover, White, & Hall, 2008;Shaw et al, 2009;Winter et al, 2017), the way that 'the balance between following rules and exercising professional expertise has become skewed' (Munro, 2011, p. 87), and a concern that supervision has been colonised by 'new public management' (Ingram, 2013;Lees, Meyer, & Rafferty, 2013;Ruch, 2011).…”
Section: Introductionmentioning
confidence: 99%